Bivalent therapeutic vaccine against HPV16/18 genotypes consisting of a fusion protein between the extra domain A from human fibronectin and HPV16/18 E7 viral antigens. Issue 1 (24th June 2020) - Arribillaga, Laura; Echeverria, Iciar; Belsue, Viriginia; Gomez, Timothy; Lozano, Teresa; Casares, Noelia; Villanueva, Lorea; Domingos-Pereira, Sonia; Romero, Pedro J; Nardelli-Haefliger, Denise; Hervás-Stubbs, Sandra; Sarobe, Pablo; et al.
Abstract : Background: In vivo targeting of human papillomavirus (HPV) derived antigens to dendritic cells might constitute an efficient immunotherapeutic strategy against cervical cancer. In previous works, we have shown that the extra domain A from murine fibronectin (mEDA) can be used to target antigens to toll-like receptor 4 (TLR4) expressing dendritic cells and induce strong antigen-specific immune responses. In the present study, we have produced a bivalent therapeutic vaccine candidate consisting of the human EDA (hEDA) fused to E7 proteins from HPV16 and HPV18 (hEDA-HPVE7-16/18) and evaluate its potential as a therapeutic vaccine against cervical cancer. Materials and methods: Recombinant fusion proteins containing HPV E7 proteins from HPV16 and HPV18 virus subtypes fused to hEDA were produced and tested in vitro on their capacity to bind TLR4 and induce the production of tumor necrosis factor-α or interleukin (IL)-12 by human monocytes and dendritic cells. The immunogenicity and potential therapeutic activity of the vaccine in combination with cisplatin or with the TLR3 agonist molecules polyinosinic‐polycytidylic acid (Poly IC) or Poly ICLC was evaluated in mice bearing subcutaneous or genital orthotopic HPV16 TC-1 tumors. Results: hEDA-HPVE7-16/18 prototype vaccine binds human TLR4 and stimulate TLR4-dependent signaling pathways and IL-12 production by human monocyte-derived dendritic cell. Vaccination with hEDA-HPVE7-16/18 induced strong HPVE7-specific Cytotoxic T lymphocyte (CTL) responses and eliminated established tumors in the TC-1-based tumor model. The antitumor efficacy was significantly improved by combining the fusion protein with cisplatin or with the TLR-3 ligand Poly IC and especially with the stabilized analog Poly ICLC. Moreover, hEDA-HPVE7-16/18+Poly ICLC induced full tumor regression in 100% of mice bearing orthotopic genital HPV tumors. Conclusion: Our results suggest that this therapeutic vaccine formulation may be an effective treatment for cervical tumors that do not respond to current therapies.